SPEECH ANALYSIS: â€œI HAVE A DREAMâ€ â€“ MARTIN LUTHER KING Jr. (Stylistical Approach) - Rohaniyah, Jaftiyatur (OKARA: Jurnal Bahasa dan Sastra, 2013)
Martin Luther King Jr. is a favorable person in America. Some famous speeches produced by him reaching a better life. One of his speech is â€˜I have dreamâ€™ which is became the best American speech of the twentieth century. This speech is full of the concept of motivation reaching the American dream. The motivation is literary viewed on how figurative language touching the context of American liberty and burning American emotion to go forward better. Beautiful words produced by Martin Luther King Jr. in this speech which is stylistically motivated American societies.